2015
DOI: 10.3892/mmr.2015.3859
|View full text |Cite
|
Sign up to set email alerts
|

Podocalyxin promotes cisplatin chemoresistance in osteosarcoma cells through phosphatidylinositide 3-kinase signaling

Abstract: Abstract. Osteosarcoma (OS) is the most common type of primary bone malignancy. The use of multiagent, intensive chemotherapy has markedly improved the long-term survival rate of patients with OS. However, chemoresistance continues to be the principal reason for poor survival and disease recurrence in patients with OS. Innate or acquired resistance to cisplatin, which is one of the most effective drugs against OS, is common. Understanding the molecular basis underlying cisplatin chemoresistance in OS cells may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…As the most common primary malignancy of bone, osteosarcoma has complicated occurrence and development which have not been clarified yet. Although development of surgery combined with neoadjuvant chemotherapy has significantly improved, the survival rate of osteosarcoma in the last few decades has plateaued, which may be heavily influenced by resistance to chemotherapy drugs (16,17). Therefore, discovery of effective ways that can increase the sensitivity to chemotherapy will be important in antitumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…As the most common primary malignancy of bone, osteosarcoma has complicated occurrence and development which have not been clarified yet. Although development of surgery combined with neoadjuvant chemotherapy has significantly improved, the survival rate of osteosarcoma in the last few decades has plateaued, which may be heavily influenced by resistance to chemotherapy drugs (16,17). Therefore, discovery of effective ways that can increase the sensitivity to chemotherapy will be important in antitumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of PODXL in HCT15 colon carcinoma cells markedly increased the sensitivity to 5-fluorouracil, an inhibitor of thymidylate synthase, and to irinotecan [54], a topoisomerase I inhibitor with reported clinical activity against relapsed or refractory B-NHL in combination chemotherapy [115,116]. Furthermore, enforced expression and PODXL silencing studies in MG-63 and U2OS osteosarcoma cell lines showed that PODXL induces cisplatin chemoresistance via PI3K/AKT signaling pathway [88]. Cisplatin is a chemotherapeutic drug effective against many types of cancers, including NHL [117].…”
Section: Podxl In Drug Resistancementioning
confidence: 99%
“…Drug resistance can be classified into two main categories: intrinsic and acquired (2,3). To devise methods and drugs that can overcome the effects of drug resistance, researchers have been focusing on elucidating the molecular mechanisms underlying the development of drug resistance which can further help in elucidating chemoresistance-related mechanisms and devising methods of preventing it.…”
Section: Introductionmentioning
confidence: 99%